Rapid prototyping of a four terminal fringing field electrical impedance spectroscopy sensor (Transactions on Additive Manufacturing Meets Medicine, 2023)
The ability of a tumor cell to metastasize, influenced by the specific cell junctions between tumor cells, is important in the mortality of cancer patients. To evaluate the electric properties of cell junctions Electrical Impedance Spectroscopy (EIS), a promising tool to analyze the cell-specific, frequency-dependent impedance of cancer cells, can be used to perform measurements during the confluent growth of the metastatic cells on the surface of a sensor. This paper aims to develop a prototype for a comb-structured, planar fringing field sensor (FFS) that can be used with four terminal (4T) EIS cell measurements. Due to the novelty of this 4T sensor, no exact design criteria are defined in literature. A rapid prototyping approach, utilizing a novel silver ink, which can be used with a desktop inkjet printer, and a material jetting printer, are used to quickly explore the design space. Design parameters for the 4T FFS are derived based on known relationships from two terminal electrodes and experimental results. Analyzing ion solution measurements of the different FFS designs, we were able to show that the relationship between the width of the digit and the gap in-between as well as the number of digits are influencing the performance of the FFS, resulting in an optimized design. With this design we were able to show the performance improvement a 4T sensor has over a 2T sensor and differentiate significantly between different ion solutions. Although desktop silver inkjet printing still has some limitations, it is a promising approach to rapidly prototype biosensors. Overall, we were able to define design parameters for optimizing the fringing field sensor performance.AcknowledgmentsThe authors would like to thank the Landesforschungsförderung Hamburg for providing financial means to support our research through the project grant LFF-GK10.Author’s statementAuthors state no conflict of interest. Informed consent has been obtained from all individuals included in this study.
Keywords: Electrical Impedance Spectroscopy; Inkjet Printing; planar Fringing Field Sensor; 3D Printing; Rapid prototyping